2006
DOI: 10.1532/ijh97.06095
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Agammaglobulinemia Diagnosed in Adulthood: A Case Report

Abstract: X-linked agammaglobulinemia (XLA) is a humoral immunodeficiency caused by mutations in Bruton's tyrosine kinase (BTK). Patients typically become symptomatic during infancy or early childhood and develop recurrent bacterial infections. We report a Japanese case of XLA diagnosed in a patient who was 27 years of age and who had no history of severe infection. The patient's serum immunoglobulin (Ig) G, IgA, and IgM levels were 132,7, and 17 mg/dL, respectively. The percentage of positive cells for CD19 and CD20 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Some authors indicated later onset of Clinical and immunological analysis of patients with X-linked agammaglobulinemia: single center experience symptoms in few cases -over 7 years of age [3]. Usuiu et al described a 27-year-old male with mild course of the disease and recurrent pneumonias since the age of 25 [7]. One of our patients had quite high IgG levels, reaching 0.4 g/l, in four -B lymphocytes reached 2% and more.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Some authors indicated later onset of Clinical and immunological analysis of patients with X-linked agammaglobulinemia: single center experience symptoms in few cases -over 7 years of age [3]. Usuiu et al described a 27-year-old male with mild course of the disease and recurrent pneumonias since the age of 25 [7]. One of our patients had quite high IgG levels, reaching 0.4 g/l, in four -B lymphocytes reached 2% and more.…”
Section: Discussionmentioning
confidence: 56%
“…The diagnosis is delayed due to less severe or even atypical courses of infection. Some authors report the diagnosis of XLA in adult patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, X-linked agammaglobulinemia, a disorder leading to profound loss of B cells, may present atypically or later in life [33,73,95,96,97,98,99,100,101,102,103,104,105,106,107] while CD40 ligand deficiency may present with deceptively unimpressive IgM levels [29]. Similarly, X-linked lymphoproliferative disorders may mimic CVID in men [108,109,110,111].…”
Section: Monogenic Disorders Mimicking Cvidmentioning
confidence: 99%
“…There have been several reports of atypical cases of XLA that were diagnosed in adulthood 1–3 . In those cases, Ig levels were moderately low and the patients did not suffer from any severe infection during their childhood.…”
Section: Serum Ig Levels and Mutations Of Btkmentioning
confidence: 99%
“…We reviewed nine Japanese patients with adult‐onset XLA, including our case (P9) (Table 1). 1–3 We classified these patients into the severe and the less severe group. The alignment of BTK families discloses that L32, T33 and R525 are highly conserved, but Y598 is not conserved (Fig.…”
Section: Serum Ig Levels and Mutations Of Btkmentioning
confidence: 99%